PENGARUH PENERAPAN GREEN CONSTRUCTION TERHADAP KINERJA LINGKUNGAN DAN EKONOMI DENGAN PERAN MEDIASI KINERJA LINGKUNGAN - Maria Elfrida Boibalan; Nectaria Putri Pramesti (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2026)
The construction sector is one of the largest contributors to global carbon emissions, making green construction a strategic approach toward achieving sustainable development. This study aims to analyze the effect of green construction implementation on environmental performance and economic performance of construction projects in Indonesia, as well as to examine the mediating role of environmental performance in this relationship. A quantitative approach using Structural Equation Modeling Partial Least Squares (SEM-PLS) was employed as the primary analytical method. Data were collected through structured five-point Likert-scale questionnaires from 150 construction professionals directly involved in green building projects in Indonesia, including project managers, consultants, contractors, and environmental specialists. The results confirm that green construction has a positive and significant effect on environmental performance (β = 0.623; p < 0.001) and economic performance (β = 0.218; p < 0.05). Environmental performance also demonstrated a positive and significant effect on economic performance (β = 0.512; p < 0.001) and partially mediates the relationship between green construction and economic performance, with a Variance Accounted For (VAF) value of 59.4%. The R² values of environmental performance (68.8%) and economic performance (57.1%) indicate substantial explanatory power of the model. These findings affirm that the success of green construction implementation in generating economic benefits is largely determined by prior environmental performance achievements as the primary mediation pathway, necessitating a holistic and integrated implementation strategy.